Pengaruh Praktik Kerja Lapangan (PKL), Self-Efficacy dan Internal Locus of Control Terhadap Kesiapan Kerja Siswa SMKN Mojoagung Jombang - Ismi Farikhatul Habibah; Renny Dwijayanti (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Vocational High School (SMK) is an educational institution that specifically aims to prepare students to be ready to work. Vocational High School graduates are expected to be able to work immediately after graduation because they are considered to have qualified abilities and skills. Therefore, job readiness is very important for Vocational School students, because Vocational High School students are one of the hopes of the community to become graduates who have competence in accordance with their areas of expertise. Many factors can affect work readiness, one of the external factors is field work practice and the internal factors are self-efficacy and internal locus of control. This study aims to determine the effect of field work practice, self-efficacy and internal locus of control on the work readiness of students at SMKN Mojoagung Jombang. This research uses descriptive quantitative research using research methods through distributing questionnaires to a population of all students in class XI BDP with a saturated sampling technique. amounted to 102 respondents. By using multiple regression analysis, the results of this study indicate that field work practice has a positive and significant effect on work readiness, self-efficacy has a positive and significant effect on work readiness, internal locus of control has a positive and significant effect on work readiness and field work practice, self -efficacy and internal locus of control have a positive and significant effect.Keywords: field work practice, self-efficacy, internal locus of control, work readiness